2018
DOI: 10.1007/s10826-018-1256-4
|View full text |Cite
|
Sign up to set email alerts
|

New Avenues for Promoting Mindfulness in Adolescence using mHealth

Abstract: There is a large evidence base supporting the efficacy of mindfulness interventions in adulthood, and growing support for the efficacy of these interventions in adolescence. Historically mindfulness interventions have been delivered in person and in groups, with recommendations for home practice being a critical part of the intervention. However, compliance with these practice recommendations in adolescence is very poor. Past studies indicate that using mobile technology to promote skill transfer to real life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 76 publications
0
20
0
1
Order By: Relevance
“…Meta-analyses of the effectiveness of online approaches are still emerging, yet the few that have been conducted have evidenced overall positive results (Ma et al 2018 ). In addition to online programs, mobile phone applications (e.g., Mindfulness Daily, The Mindfulness App, Headspace, Calm) have been shown to be effective supplements to interventions (Lucas-Thompson et al 2019 ). Consistent with this, mindfulness combined with the delivery of structured or unstructured intervention through text messages (ecological momentary intervention (EMI); ecological momentary assessment (EMA)), followed with frequent evaluation, encourages and empowers youth to use acquired mindfulness tools in alternate settings.…”
Section: Telehealth Interventions For At-risk Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses of the effectiveness of online approaches are still emerging, yet the few that have been conducted have evidenced overall positive results (Ma et al 2018 ). In addition to online programs, mobile phone applications (e.g., Mindfulness Daily, The Mindfulness App, Headspace, Calm) have been shown to be effective supplements to interventions (Lucas-Thompson et al 2019 ). Consistent with this, mindfulness combined with the delivery of structured or unstructured intervention through text messages (ecological momentary intervention (EMI); ecological momentary assessment (EMA)), followed with frequent evaluation, encourages and empowers youth to use acquired mindfulness tools in alternate settings.…”
Section: Telehealth Interventions For At-risk Youthmentioning
confidence: 99%
“…A study by Lindsay et al ( 2018 ) was the first to show that brief smartphone-based mindfulness training can impact objective biological stress outcomes, including blood pressure (treatment vs. control: χ 2 (1) = 10.16, p = 0.001, d = 0.72) and cortisol levels (treatment vs. control: F (1,140) = 4.79, p = 0.030, d = 0.47). Lucas-Thompson et al ( 2019 ) found improvement in well-being of youth at risk for NSSI and suicidal ideation using mindfulness and EMIs. Though research in this area is emerging, the use of these kinds of apps appears to be promising for use with the adolescent population (Nock et al 2009 ).…”
Section: Telehealth Interventions For At-risk Youthmentioning
confidence: 99%
“…These studies indicate that MBIs delivered online, through self-help or individually guided learning, or through a smartphone application, can increase mindfulness and lower psychological symptoms (13,14,(33)(34)(35)(36)(37)(38). Therefore, despite potential challenges of incorporating technology into an MBI [for a review, see (15)], we argue that an important next step in the implementation of MBIs is to incorporate an EMI, particularly when working to increase adolescent mindfulness. In the current paper, we discuss the development and content of a multi-method, adaptive supplement to an evidence-based MBI for adolescents.…”
Section: The Case For Incorporating Technology Into An Mbi For Adolesmentioning
confidence: 99%
“…Despite the power of these EMI supplements, as far as we are aware, no empirically supported EMIs are available for mindfulness-based group interventions. As such, it is important to develop an evidence-based and empirically supported EMI supplement to mindfulness-based group interventions to maximise potential to support long-term positive change for adolescents 35…”
Section: Introductionmentioning
confidence: 99%